167 The Experience and Outcomes of Elective Urgent and Cancer Surgery in A District General Hospital in The United Kingdom During Covid-19 Pandemic. (4th May 2021) - Tam, A; Elhadi, M; Ong, C T; Bhat, A; Akhtar, M
Abstract: Background: Many urgent and elective surgeries were postponed to cope with the Coronavirus disease (COVID-19) pandemic, with latest data found a substantial postoperative mortality risk (25·6%, 18.9%) after emergency and elective surgery, respectively. Our institution was one of the first trust to offer essential elective surgery using a "COVID-free" designated site during the start of the pandemic. The aim of this study is to analyse the clinical outcomes of patients who underwent essential elective procedures during the virus outbreak in the UK. Method: Retrospective analysis of outcomes all patients who had undergone urgent elective and cancer surgery, from 30 th March 2020 to 21 st May 2020, using an implemented "Super Green Pathway". The primary endpoints were 30 days mortality and COVID related morbidities, and the secondary endpoints were surgical related complications and oncological outcomes. Results: 92 patients (Male:45%; Female:55%) across 5 surgical specialties were identified. There was no record of mortality in our cohort. Only 1 patient was tested positive for SARS-CoV-2, 18 days after the initial operation without any pulmonary complications. Conclusions: It is possible to mitigate the high mortality risk of postoperative complications associated with COVID-19, with no delay to essential surgeries for cancer patients, thus delivering safe practice during the pandemic.